Al-Azhar Madrasa (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
Al-Azhar Madrasa, also known as Al-Azhar University, holds an esteemed position as one of the oldest and most prestigious centers of Islamic education in the world. Established in 970 AD in Cairo, Egypt, Al-Azhar has evolved from its Shia origins to become a leading Sunni institution, fostering a tradition of academic excellence and producing distinguished scholars for over a millennium. This article delves into the historical significance of Al-Azhar Madrasa, its rigorous academic standards, and its crucial role in shaping Islamic intellectual heritage. It also explores the challenges the institution has faced in adapting to the modern era, particularly in navigating issues of extremism and interfaith dialogue. Despite the trials it has encountered, Al-Azhar continues to shine as a beacon of knowledge, promoting a moderate and tolerant interpretation of Islam while embracing both its traditional roots and contemporary relevance in the ever-changing world.